Impact of Weeds on Paddy Biomass in Upland Rainfed Areas of Terai Region of Nepal - Bhatt, M. D.; Singh, S. P.; Tewarir, A. (Ecoprint: An International Journal of Ecology, 2009)
Field experiments were conducted to analyze impacts of weeds on biomass of two varieties of rain fed upland paddy (cv. Radha-4 and Neemai) during the Kharif session of 2004-2005 in the Terai region of Nepal. Four experiments were conducted in randomized block design with three replications. A total of 55 weed species were identified with densities of 240 individual plants per sqm in Radha-4 and 236 individual plants per sqm in Neemai. The annual net primary productivity of paddy crop was maximum (2329.3 g m-2 yr-1 in Radha-4 and 2170.3 g m-2 yr-1 in Neemai) in weed-free plots and lowest (1659.8 g m-2 yr-1 in Radha-4 and 1659.4 g m-2 yr-1 in Neemai) in unweeded plots. Hand weeding was done twice at 25 and 50 days after broadcasting and proved to be better than herbicides in the paddy biomass. The mean maximum biomass of paddy in weed free plots was 2418.7 and 2270.3 g m-2 in Radha-4 and Neemai. This biomass was similar to twice hand weeded plots being 1% lower in both the varieties. Compared to weed-free plots the biomass reduction in Radha-4 and Neemai in herbicides treated plots was lower by 1.4% in both the varieties. Compared to weed-free plots the biomass reduction in unweeded plots was recorded 29% lower in Radha-4 and 23% in Neemai. The weed biomass was highest in unweed plots (516.4 and 436.6 g m-2) and lowest (169.3 and 192.3g m-2 in twice hand-weeded plots. The net annual primary productivity of weeds was highest (437.9 g m>-2 yr-1 in Radha-4 and 376.6 g m-2 yr-1 in Neemai) in unweeded plots and lowest (119.7 g m-2 yr-1 in Radha-4 and 145.5 g m-2 yr-1 in Neemai) in twice hand weeded plots. The trend of grain yield in both the varieties were; weed-free plots (TT) > twice hand-weeded plots (T1) > chemical fertilizer and butachlor plots (T2) > unweeded plots (To). Key words: Paddy; weeds; upland; biomass; Terai doi: 10.3126/eco.v13i0.1623 Ecoprint (An International Journal of Ecology) Vol. 13, No. 1, 2006 Page 15-22